NAFLD as a continuous driver in the whole spectrum of vascular disease. (February 2022) - Li, Wei; Liu, Jiayi; Cai, Jingjing; Zhang, Xiao-jing; Zhang, Peng; She, Zhi-gang; Chen, Shaoze; Li, Hongliang
Abstract: Vascular disease is the prime determinant to cardiovascular morbidities and mortalities, which comprises the early vascular damage and subsequent cardiovascular events. Non-alcohol Fatty Liver Disease (NAFLD) is a systemic metabolic disorder that drives the progression of vascular disease through complex interactions. Although a causal relationship between NAFLD and cardiovascular disease (CVD) has not been established, a growing number of epidemiological studies have demonstrated an independent association between NAFLD and early vascular disease and subsequent cardiovascular events. In addition, mechanistic studies suggest that NAFLD initiates and accelerates vascular injury by increasing systemic inflammation and oxidative stress, impairing insulin sensitivity and lipid metabolism, and modulating epigenetics, the intestinal flora and hepatic autonomic nervous system; thus, NAFLD is a putative driving force for CVD progression. In this review, we summarize the clinical evidence supporting the association of NAFLD with subclinical vascular disease and cardiovascular events and discuss the potential mechanisms by which NAFLD promotes the progression of vascular disease.